The patterns of trade between the ASEAN and ANZCERTA countries in agricultural products : a thesis presented in partial fulfilment of the requirements for the degree of Master of Applied Economics at the Department of Applied and International Economics, Massey University - Zamroni, Zamroni (Massey University, 2003)
A gravity model of trade could explain the trade patterns of countries, supported by either the dominance of factor endowments or economies of scale as sources of trade. The gravity model is based on the principle that the trade flows between two trading countries is positively related to their economic size, represented by their GDP and population, and inversely related to the distance between them. By using data from the period 1965-1999, this study applies the gravity model to identify empirically the determinants of agricultural trade among five member countries of the Association of Southeast Asian Nations (ASEAN): Indonesia, Malaysia, the Philippines, Singapore and Thailand; and also between the Australia-New Zealand Closer Economic Relations Trade Agreement (ANZCERTA) countries, vis-à-vis Australia and New Zealand. The variables used to identify the trade patterns between these two groups are: the incomes of exporting and importing countries, populations of exporting and importing countries, distances between them, and some other augmented variables. Distance has been found to be an impediment to trade for all five ASEAN countries, but not for the two ANZCERTA countries. The level of competitiveness, which is represented by the real exchange rate, was found to be significant in respect of agricultural trade. The Asian financial crisis was not found to have significant effects on agricultural trade of most ASEAN countries or of the ANZCERTA countries. The effect of a country's membership of ASEAN varied from one member country to another. The ANZCERTA membership, likewise, did not affect significantly the observed trade patterns between Australia and New Zealand. Furthermore, the ASEAN Free Trade Area (AFTA)-ANZCERTA relationship also did not have a significant effect on the trade patterns of the ASEAN and ANZCERTA countries. Intra-industry trade (IIT) involving agricultural products among ASEAN countries is relatively low. Agricultural trade of the five ASEAN and the two ANZCERTA countries could be classified as strongly inter-industry, not intra-industry, on the basis of the findings. Generally, the IIT patterns of the ASEAN and ANZCERTA countries with their trading partners increased gradually from 1965 to 1999, but are still quite low, so that inter-industry trade still characterises the exchange of agricultural products among these countries.
Keywords: New Zealand; Australia; ASEAN countries -- Commerce; Produce trade; Agriculture -- Economic aspects